Changes of functional brain network topology associated with nutritional indicator of patients with recurrent major depressive disorder - Liu, Guanghui; Jiang, Yanli; Zhou, Chunpeng; Wang, Xiangxiang; Dai, Min; Zhang, Jinping; Yu, Jing; Zhang, Gangzhong (Frontiers in Nutrition, 2025)
IntroductionMajor depressive disorder (MDD) is generally categorized into first-episode MDD (fMDD) and recurrent MDD (rMDD). This study aimed to investigate the changes of brain network, as well as the relationships between relapses, brain regions, nutritional and metabolic indicators by resting-state functional magnetic resonance imaging (rs-fMRI) and graph theoretical analysis.MethodsThirty-two fMDD patients, 32 rMDD patients, and 32 healthy controls (HCs) underwent rs-fMRI scanning. Graph theoretical analysis was applied to examine the nodal strength and nodal global efficiency of brain networks. In addition, the nutritional and metabolic indicators were acquired from all patients. The differences of demographic, clinical data and topological parameters between groups were compared. Moreover, the relationships between number of relapses, topological parameters of brain regions, nutritional and metabolic indicators were evaluated.ResultsPatients with rMDD showed decreased level of brain-derived neurotrophic factor (BDNF) when compared with those with fMDD. Both fMDD and rMDD patients showed decreased nodal strength and global efficiency in the left amygdala compared to HCs. Additionally, rMDD patients exhibited more extensive network disruptions, including decreased nodal strength in the right middle frontal gyrus, left middle cingulate gyrus, left posterior cingulate gyrus, left hippocampus, and right amygdala, as well as decreased nodal global efficiency in multiple regions involved in emotional processing and cognitive control. Moreover, the number of episodes were negatively associated with the level of BDNF, nodal strength of right amygdala and nodal global efficiency of right amygdala of rMDD patients. The level of BDNF were positively related to nodal strength of right amygdala and nodal global efficiency of right amygdala of rMDD patients.ConclusionOur findings revealed distinct patterns of brain network topology between fMDD and rMDD patients, with rMDD patients showing more widespread disruptions, which might be associated with greater number of relapses and worse level of neurological nutrition. These results suggested that recurrent depressive episodes might related to progressive disruptions in brain, particularly in regions involved in emotional processing and regulation.